Hemostatic Findings in Ascitic Fluid: A Cross‐Sectional Study in 70 Dogs. (16th November 2016) - Zoia, A.; Drigo, M.; Piek, C.J.; Simioni, P.; Caldin, M.
Abstract : Background: Ascitic fluids of horses and humans have fibrinolytic activity, independent of the underlying mechanism of fluid formation. Objective: To determine whether coagulation and fibrinogenolytic/fibrinolytic activity (ie, low fibrinogen and increased fibrin–fibrinogen degradation products [FDPs], D‐dimer, or both) occur in all types of ascitic fluid in dogs. Animals: A total of 70 client‐owned dogs with ascites. Methods: In this cross‐sectional study, dogs were categorized based on the pathophysiology of fluid formation into 4 groups: transudates due to decreased osmotic pressure, transudates due to increased hydrostatic pressure, exudates, and hemorrhagic ascites. Fibrinogen, FDPs, and D‐dimer concentrations were measured and then compared in both ascitic fluid and plasma. Results: Ten dogs had transudates due to decreased colloid osmotic pressure, 18 had transudates due to increased hydrostatic pressure, 13 had exudates, and 29 had hemorrhagic ascites. Ascitic fibrinogen concentrations (n = 70) were significantly lower (median = 59 mg/dL; range: 59–122 mg/dL) than those in the plasma (median = 168 mg/dL, range: 59–879 mg/dL; P < .0001). Ascitic FDPs concentrations (n = 70) were significantly higher (<5 μg/mL: 3/70 dogs, ≥5 to <20 μg/mL: 11/70 dogs, ≥20 μg/mL: 56/70 dogs) than those in the plasma (<5 μg/mL: 17/70 dogs, ≥5 to <20 μg/mL: 28/70 dogs, ≥20 μg/mL: 25/70 dogs; P < .0001). Ascitic D‐dimer concentrations (n = 70) were significantly higher (median = 3.98 μg/mL, range: 0.02–9.19) than those in the plasma (median = 0.11 μg/mL, range: 0.01–4.08; P < .0001). Analysis of the data for each of the 4 different types of ascites showed similar results to those of all the data analyzed together. Conclusions and Clinical Importance: Ascitic fluid of dogs has evidence of coagulation activation and fibrinogenolytic/fibrinolytic activity and that this phenomenon occurs independent of the underlying mechanism that leads to the formation of ascites.